2000
DOI: 10.1084/jem.192.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Murine Thymic Stromal Lymphopoietin (Tslp) Receptor

Abstract: The cellular receptor for murine thymic stromal lymphopoietin (TSLP) was detected in a variety of murine, but not human myelomonocytic cell lines by radioligand binding. cDNA clones encoding the receptor were isolated from a murine T helper cell cDNA library. TSLP receptor (TSLPR) is a member of the hematopoietin receptor family. Transfection of TSLPR cDNA resulted in only low affinity binding. Cotransfection of the interleukin 7 (IL-7)Rα chain cDNA resulted in conversion to high affinity binding. TSLP did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 367 publications
(150 citation statements)
references
References 39 publications
1
141
1
Order By: Relevance
“…Thus, precursors from ␥c-deficient mice do not respond to IL-7 but respond to TSLP, whereas precursors isolated from IL-7R␣-deficient mice respond to neither IL-7 nor TSLP (31).…”
Section: Tslp Can Drive the Generation Of B1 Cells From Fl Precursorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, precursors from ␥c-deficient mice do not respond to IL-7 but respond to TSLP, whereas precursors isolated from IL-7R␣-deficient mice respond to neither IL-7 nor TSLP (31).…”
Section: Tslp Can Drive the Generation Of B1 Cells From Fl Precursorsmentioning
confidence: 94%
“…Discussion TSLP was initially described as a cytokine able to drive B lymphocyte differentiation (17). In the past 3 years a renewed interest in the biological activities of this cytokine occurred, after the publication of its sequence (37), the characterization of its receptor complex (30,31), and the description of its activity on human dendritic cells (38,39). We reported recently that TSLP is able to support B lymphocyte production from FL, but not adult BM, pro-B cells (19) and showed that TSLP is responsible for the vast majority of the B lymphocytes that are generated in the absence of IL-7 signaling (19,21,32).…”
Section: Tslp Supports the Proliferation Of Adult Large Pre-b But Nomentioning
confidence: 99%
“…A third group identified it as an expressed sequence tag (EST) that had substantial homology to the erythropoietin receptor cytoplasmic domain, but then it was directly demonstrated that this orphan receptor was in fact the elusive TSLPR (59). Another group reported the cloning of TSLP as well as its receptor (60,63). TSLP only weakly binds to TSLPR but exhibits higher affinity to the combination of TSLPR and IL-7R␣.…”
Section: Il-7 and Tslp And The Sharing Of Il-7ramentioning
confidence: 99%
“…Interestingly, the receptor for TSLP contains its own distinctive receptor chain, TSLPR, as well as IL-7R␣ (59,60). Thus, TSLP and IL-7 share IL-7R␣ as a common receptor component (Fig.…”
Section: Il-7 and Tslp And The Sharing Of Il-7ramentioning
confidence: 99%
“…The TSLP receptor complex is a heterodimer that consists of a low-affinity ligand binding chain, the TSLP receptor (TSLPR), and the IL-7 receptor ␣ chain (IL-7R␣) (5,6). TSLP and TSLPR have also been identified and characterized in humans, and the human TSLP receptor complex has been shown to also be a heterodimer that is composed of the TSLPR and IL-7R␣ chains (7,8).…”
mentioning
confidence: 99%